MUSHAF AL-QUR'AN KOLEKSI H. SYU’AIB TRANGKIL PATI: Migrasi, Komodifikasi Naskah, Serta Analisis Rasm dan Ḍabṭ - Ni'mah, Arifatun; Asif, Muhammad (AL ITQAN: Jurnal Studi Al-Qur'an, 2021)
This paper focuses on the study of the manuscript text of  H. Syu'aib collection from the village of Asempapan, Trangkil, Pati. This study aims to analyze the writing rules used in copying manuscripts at the time in the region. This research is qualitative with a philological approach. viewed from the perspective of rasm and ḍabṭ Ghānim Qaddūrī. This manuscript uses a mixed Rasm between Rasm imlā'i and Rasm uthmānī both from the rules of removal and addition of letters. While the writing of hamzah, badl, faṣl and waṣl generally uses rasm utmānī. However, some writings were found not match with the two rasm rules, such as the rules for removing letters, connecting and separating sentences that caused idghām. This discrepancy seems to be caused of no rule for reference in writing  manuscripts in Nusantara therefore the copyists of some manuscripts only relied on rote memorization. This finding shows that the copying of manuscripts in the particular region, even in Indonesia, generally does not always use the two rasm both are uthmānī and imlā'i which are the benchmarks in the general Islamic world. This study also highlights the commodification and migration of manuscripts in the region.